Germanisms in the Old-Belarusian language against the background of the Old-Polish language and their reflection in the Old-Ukrainian and Old-Russian languages - Pryhodzich, Mikalai R. (Journal of the Belarusian State University. Philology, 2022)
The article examines the original Germanisms borrowed by the Old-Belarusian language during the 14th–18th centuries both directly from the Germanic languages and through the Old-Polish language, the parallels of the corresponding units in the Old-Ukrainian and Old-Russian languages are analysed. Based on the preliminary results of the international project called «Migrating words: ways of German borrowings from Polish to East Slavic languages» (project leader is Professor of the Carl von Ossietzky University of Oldenburg Gerd Hentschel), quantitative and temporal parameters of borrowing such words, their distribution in the monuments of Old-Belarusian writing on the material of the card index and directly 37 issues of «Historical dictionary of Belarusian language» are determined. Attention is drawn to the possibility of borrowing Germanisms by the Old-Russian language through the mediation of the Old-Belarusian language, the need for further research of the place and role of Germanisms in the lexical composition of the modern Belarusian literary language in connection with the preparation of a multi-volume edition of a new explanatory dictionary is indicated.
Keywords: Old-Belarusian language; interlanguage contacts; Germanisms; direct borrowing; Old-Polish language; Old-Ukrainian language; Old-Russian language; foreign borrowings in the modern Belarusian literary language